EXPLORING THE CORRELATION BETWEEN MOTIVATION AND WRITING PROFICIENCY IN SEVENTH-GRADE EDUCATION - Ni Putu Deana Eka Putri; I Ketut Wardana; I Gusti Agung Putri Wirastuti (Academic Journal on English Studies (AJOES), 2023)
The purpose of this research was to find out the correlation between motivation and writing skill of the seventh-grade students of SMPN 1 Kuta Utara in the academic year 2023/2024. There were two variables in the present research. The independent variable was motivation and the dependent variable was writing skill. The population of this study was the seventh-grade students of SMPN 1 Kuta Utara. The sample of this study was 70 students which were taken with a cluster random sampling method. The design of this study was an ex post facto research correlational study. Furthermore, the matching questionnaire and writing test were used as the research instrument. The research instruments were made in order to collect the required data. The data were then analysed by using SPSS 26 version. There were two steps in analysing the data, namely pre-requisite analysis and hypothesis testing. The hypothesis testing was conducted by applying Pearson Product Moment Correlation and T-test. Based on the finding, it was found the correlation coefficient were 0.931 that means there is a significant correlation between motivation and writing skill of the seventh-grade students of SMPN 1 Kuta Utara in academic year 2023/2024.